Social capital and institutional constraints : a comparative analysis of China, Taiwan and the US - Son, Joonmo (Routledge contemporary China series., 2012)
The sociological concept of social capital has grown in popularity in recent years and research programs in North America, Europe, and East Asia have demonstrated how social capital has a significant impact on occupational mobility, community building, social movement, and economic development. This book uses new empirical data to test how social capital works in different societies with diverse political-economic and cultural institutions. Taking a comparative approach, this study focuses on data from three different societies, China, Taiwan, and the United States, in order to revea.